Phenotyping and diversity assessment of Dendrobium species by using DUS guidelines - Reddy, D Mahesh; Momin, kalkame ch; Bhargav, V; Kumar, Sunil; Singh, Amit Kumar; Arun Kumar, Ph (Plant Science Today, 2025)
Dendrobiums are sympodial epiphytic orchids belonging to the family Orchidaceae. and have an extraordinary variation in bloom shape, size and colour. They are widely recognized for their enchanting beauty and longlasting quality. Morphological characterization of Dendrobium species was carried out using the DUS guidelines developed by the Protection of Plant Varieties and Farmers Rights Authority (PPV and FRA) in New Delhi. A total of 15 Dendrobium species were characterized for 52 vegetative and floral traits. Among the 52 traits, 8 were monomorphic, 12 were dimorphic and 32 were polymorphic, indicating their potential for characterization. Principal component analysis showed 86.14% variation in the first 4 principal components with an eigenvalue >1.0. The first and second principal components explained 41.43% and 19.45% of the total variation respectively. The dendrogram produced by a Ward analysis validated the Principal Component Analysis (PCA) findings. The Dendrobium species were grouped into 2 major clusters with three sub-clusters based on the correlation between the morphological traits among the species. Characterization established distinctiveness amongst the Dendrobium species. Breeders/farmers can use this study to distinguish between different species and apply for protection through the PPV and FR Authority, New Delhi. The trait-specific data generated while characterizing can be used to develop new inter-specific hybrids, which are common in orchids.